Pengaruh Faktor Ekspektasi Kinerja, Nilai Harga, Motivasi Hedonis dan Sosial terhadap Minat Masyarakat Kabupaten Buleleng dalam Penggunaan Mobile Banking - Wirasmini, Tri Candra Martyana; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of performance expectations, price values, hedonic and social motivations on people's interest in using mobile banking. The method in this research is associative quantitative method with primary data. The sample used was 346 people of Buleleng Regency aged 20-24 who were selected through purposive sampling technique. Determination of the number of samples is done with the tables of Isaac and Michael. The research data were processed and analyzed by multiple linear regression analysis. The results of the study stated that each variable of performance expectation, price and social value had a positive and significant effect on people's interest in using mobile banking. Meanwhile, the hedonic motivation variable has no influence on people's interest in using mobile banking. All independent variables in this study were explained by the theory of UTAUT 2 (Unified Theory of Acceptance and Use of Technology).